EGFR Mutated Lung Adenocarcinoma with Secondary Glaucoma as Early Manifestation: A Case Report - Ida Ayu Jasminarti Dwi Kusumawardani; Venny Singgih; Ni Wayan Candrawati; Putu Yuliawati; Herman Saputra; I Gusti Ayu Sri Mahendra Dwi (Jurnal Respirasi, 2021)
Background: Orbital metastases are rare in pulmonary adenocarcinoma and can be manifested as glaucoma.Case: A 64-year-old male patient complained of swelling, redness, painful and protruded left eye. Physical and radiological examination revealed mass in the right lung, retrobulbar intraconal mass of the left oculi, and metastases in the ribs, liver, brain, and vertebrae. Result of bronchial mucosal biopsy showed adenocarcinoma. Epidermal growth factor receptor (EGFR) mutation examinations detected exon 19 deletions, therefore Gefitinib was given. Left orbital exenteration was performed and obtained a biopsy result of adenocarcinoma metastases.Conclusion: Orbital metastasis occurs by hematogenous pathway due to direct access of systemic circulation to left orbital blood flow. Glaucoma as a symptom of orbital metastases can appear before primary tumor symptoms, because lung cancer often does not show specific symptoms until advanced stage. Definitive treatment consists of targeted therapy and surgical management for metastases.